Falhas e precisão experimental na avaliação dos rendimentos de grãos verdes e secos de milho - SILVA, PAULO SERGIO LIMA E; Diniz Filho, Edimar Teixieira; Rocha, Edna Lúcia da; Duarte, Severino Ramos (Revista Ceres, 2015)
-